The Regulatory RNA ern0160 Confers a Potential Selective Advantage to Enterococcus faecium for Intestinal Colonization - Reissier, Sophie; Le Neindre, Killian; Bordeau, Valérie; Dejoies, Loren; Le Bot, Audrey; Felden, Brice; Cattoir, Vincent; Revest, Matthieu (Frontiers in Microbiology, 2021)
The aim of this study was to evaluate the role of the regulatory small RNA (sRNA) Ern0160 in gastrointestinal tract (GIT) colonization by Enterococcus faecium. For this purpose, four strains of E. faecium were used, Aus0004 (WT), an ern0160-deleted Aus0004 mutant (Δ0160), a trans-complemented Δ0160 strain overexpressing ern0160 (Δ0160_0160), and a strain Δ0160 with an empty pAT29 vector (Δ0160_pAT29). Strains were studied both in vitro and in vivo, alone and in competitive assays. In in vitro experiments, no difference was observed between WT and Δ0160 strains cultured single while Δ0160_0160 strain grew more slowly than Δ0160_pAT29. In competitive assays, the WT strain was predominant compared to the deleted strain Δ0160 at the end of the experiment. Then, in vivo experiments were performed using a GIT colonization mouse model. Several existing models of GIT colonization were compared while a novel one, combining ceftriaxone and amoxicillin, was developed. A GIT colonization was performed with each strain alone and no significant difference was noticed. By contrast, significant results were obtained with co-colonization experiments. With WT + Δ0160 suspension, a significant advantage for the WT strain was observed from day 5 to the end of the protocol, suggesting the involvement of ern0160 in GIT colonization. With Δ0160_0160 + Δ0160_pAT29 suspension, the strain with the empty vector took the advantage from day 3 to the end of the protocol, suggesting a deleterious effect of ern0160 overexpression. Altogether, these findings demonstrate the potential implication of Ern0160 in GIT colonization of E. faecium. Further investigations are needed for the identification of sRNA target(s) in order to decipher underlying molecular mechanisms.